DISRUPSI: ANCAMAN ATAU PELUANG BAGI EKSISTENSI BUDAYA LOKAL? (Tinjauan Filosofis Atas Proses Perubahan Budaya) - Firgianus Botu (Aggiornamento, 2022)
On the one hand, the process of change that occurs in the era of disruption is seen as a threat and on the other hand can be used as an opportunity to create something new, more effective, efficient, and useful. I started this paper by looking at the current reality. There are many young people who experience an identity crisis and do not show a sense of love for local culture. At the same time, there was an era of disruption which was able to change everything briefly without supporting aspects as shown in the process of changing the culture of a particular society. The threat in the era of disruption can actually be used as an opportunity to create something that is more useful and effective for survival together. I use the text interpretation method in completing this paper. Text interpretation is carried out by looking at the text on the discussion of the process of cultural change and the text on the explanation of the era of disruption. The findings in this paper are dedicated to the wider community, so that they realize that currently local culture is on the threshold of extinction.